Exploring the Magnetic and Electrocatalytic Properties of Amorphous MnB Nanoflakes - Fu, B.; Tzitzios, V.; Zhang, Q.; Rodriguez, B.; Pissas, M.; Sofianos, Veronica (MDPI, 2023)
Two-dimensional (2D) metal borides are a class of ceramic materials with diverse structural and topological properties. These diverse material properties of metal borides are what forms the basis of their interdisciplinarity and their applicability in various research fields. In this study, we highlight which fundamental and practical parameters need to be taken into consideration when designing nanomaterials for specific applications. A simple one-pot chemical reduction method was applied for the synthesis of manganese mono-boride nanoflakes at room temperature. How the specific surface area and boron-content of the as-synthesized manganese mono-boride nanoflakes influence their magnetic and electrocatalytic properties is reported. The sample with the highest specific surface area and boron content demonstrated the best magnetic and electrocatalytic properties in the HER. Whereas the sample with the lowest specific surface area and boron content exhibited the best electric conductivity and electrocatalytic properties in the OER.